Sagittal Abdominal Diameter as the Best Predictor of Metabolic Syndrome in HIV-Infected Men on Antiretroviral Therapy - Drvendžija, Zorka; Galić, Biljana Srdić; Vujanović, Miloš; Marić, Daniela; Jovanović, Nina Brkić; Brkić, Snežana; Turkulov, Vesna; Ilić, Dalibor (Current HIV Research, 2024)
Background: The interaction of human immunodeficiency virus (HIV), host and antiretroviral therapy (ART) causes a range of metabolic disorders that can be characterized as a metabolic syndrome (MetS) that increases the cardiovascular risk. MetS involves central obesity, which can be detected using different anthropometric parameters. Objective: To assess the abilities of different anthropometric parameters in the prediction of MetS in HIV-infected men on ART. Method: The study involved 92 male participants (mean age 44.46±10.38 years), divided into two groups: with and without MetS. All subjects underwent biochemical evaluation (triglycerides, HDL-cholesterol, fasting glucose), blood pressure measurement and anthropometric assessment: body mass, body height, body mass index (BMI), body fat mass, body circumferences (chest, upper arm, forearm, waist, hip, proximal and middle thigh and calf), sagittal abdominal diameter (SAD), skinfold thicknesses (subscapular, anterior and posterior upper arm, anterior and lateral forearm, abdominal, supraspinal, thigh and calf), waist-to-hip ratio (WHR), waist-to-height ratio (WHtR), waist-to-thigh ratio (WTR), sagittal abdominal diameter-to-body height ratio (SADH), body adiposity index (BAI) and conicity index. MetS was specified according to IDF criteria. Results: Subjects with MetS had statistically significant higher values of all anthropometric parameters except middle thigh circumference, calf skinfold and body height. According to ROC analysis and Binary Logistic Regression, SAD has been shown as the best predictor of MetS with a predictive value of 21.40 cm (AUC:0.91), followed by WHR with a predictive value of 0.93. Conclusion: Sagittal abdominal diameter is the strongest anthropometric indicator of MetS in HIV-infected patients on ART.
Keywords: cardiovascular risk